Analysis of Legal Certainty of Sugar Import Corruption from the Perspective of Minister of Trade Regulation Number 117 of 2015 (Case Study of Decision Number 55/PID.SUS-TPK/2025/PT DKI) - Joni Antono; Ernawati Ernawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The normative ambiguity in Articles 6 and 7 of the Minister of Trade Regulation Number 117 of 2015 creates room for interpretation regarding the state of emergency. This ambiguity has created legal uncertainty in the sugar import corruption case, as reflected in Decision Number 55/PID.SUS-TPK/2025/PT DKI. This study aims to analyze the construction of the state of emergency in the regulation and evaluate the application of the elements of the crime of corruption in the court decision from the perspective of legal certainty. The research method used is a juridical-normative approach with a statutory regulatory approach and a case approach, using Jan M. Otto's theory of legal certainty and the doctrine of the state of necessity as analytical tools. The results show that Permendag 117/2015 contains a normative gap regarding the limits of the state of emergency, which triggers the criminalization of the policy. Furthermore, the application of the elements of abuse of authority and state losses in the decision does not meet the principle of legal certainty because it is based on potential losses and ignores the validity of valid administrative permits.